Isothermal Austenite–Ferrite Phase Transformations and Microstructural Evolution during Annealing in Super Duplex Stainless Steels - Andrea Francesco Ciuffini; Silvia Barella; Cosmo Di Cecca; Andrea Gruttadauria; Carlo Mapelli; Davide Mombelli (Metals, 2017)
Super Duplex Stainless Steels (SDSSs) are composed of α-ferrite and γ-austenite grains, the simultaneous presence of which forms an optimal microstructure to achieve the best combination of mechanical and corrosion resistance properties. Moreover, international quality standards are strict about the phase fraction ratio. The purpose of this work is the achievement of a better description of the phase ratio evolution taking place during annealing at 1080 °C in the super duplex stainless steels F53–S32750 and F55–S32760. The experimental results show a damped sinusoidal trend in the α/γ phase ratio evolution with the increase of the soaking time of thermal treatment. This can be described by coupling both the competitive coarsening growth regime and the concept of the local equilibrium phase transformations, pointing out a good correspondence with the experimental data. Further, recrystallization phenomena also play a major role. Finally, the additivity character of the observed processes has been proven.